2008
DOI: 10.1186/1741-7015-6-23
|View full text |Cite
|
Sign up to set email alerts
|

Increased deposition of C3b on red cells with low CR1 and CD55 in a malaria-endemic region of western Kenya: Implications for the development of severe anemia

Abstract: Background: Severe anemia due to Plasmodium falciparum malaria is a major cause of mortality among young children in western Kenya. The factors that lead to the age-specific incidence of this anemia are unknown. Previous studies have shown an age-related expression of red cell complement regulatory proteins, which protect erythrocytes from autologous complement attack and destruction. Our primary objective was to determine whether in a malaria-endemic area red cells with low levels of complement regulatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 34 publications
8
42
0
Order By: Relevance
“…Studies conducted in areas of P. falciparum endemicity have documented that higher levels of CR1 and CD55 are exhibited in RBCs from children with uncomplicated malaria or who are uninfected than in RBCs from those with severe anemia (119)(120)(121). Furthermore, a study conducted on susceptible children in western Kenya demonstrated an association between low levels of complement regulatory proteins on RBC surfaces and increased risk of C3 deposition on their membranes (125). These data suggest that lower expression levels of such biomarkers would contribute to an increased clearance of erythrocytes, leading to anemia in falciparum malaria.…”
Section: The Complement System and Malariamentioning
confidence: 99%
“…Studies conducted in areas of P. falciparum endemicity have documented that higher levels of CR1 and CD55 are exhibited in RBCs from children with uncomplicated malaria or who are uninfected than in RBCs from those with severe anemia (119)(120)(121). Furthermore, a study conducted on susceptible children in western Kenya demonstrated an association between low levels of complement regulatory proteins on RBC surfaces and increased risk of C3 deposition on their membranes (125). These data suggest that lower expression levels of such biomarkers would contribute to an increased clearance of erythrocytes, leading to anemia in falciparum malaria.…”
Section: The Complement System and Malariamentioning
confidence: 99%
“…The current findings on the functional consequence of RBC CR1 ligation in the immune-transfer process are important especially now when unexpected and non-redundant roles for human RBC CR1 in pathologies ranging from malaria (45) and sepsis (46) to Alzheimer disease (35,(47)(48)(49) are beginning to be unraveled.…”
Section: Discussionmentioning
confidence: 99%
“…Data derived from naturally infected individuals also indicate that after parasite clearance the erythrocyte life span is reduced in patients recovering from P. falciparum or P. vivax malaria (57,58). Hypotheses put forth for the destruction of uninfected erythrocytes have focused on different possible mechanisms including reduced erythrocyte deformability (59,60), accelerated erythrocyte senescence (61), and immunologic removal (62)(63)(64)(65)(66), although none have been conclusively proven to be the mechanism.…”
Section: Fig 11mentioning
confidence: 99%